The Development of Learning Video Based on Micro-Learning Principle Towards Science Subject in Junior High School - I Made Chandra Adhipertama; I Nyoman Jampel; I Gde Wawan Sudatha (Indonesian Journal Of Educational Research and Review, 2020)
Learning videos can attract the students' interest and facilitate them during the learning process. The use of learning media is an alternative in the process of developing better learning instruction. This study aims to analyze and develop instructional video products based on the principles of microlearning in Science subjects. The data collection methods used were observation, interview, document recording, and questionnaires. This development research used the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The data generated in this research were qualitative and quantitative. The review result given by the learning content expert was in the category of very excellent with its percentage of 95%. The reviews by learning design experts obtained an excellent category, and the percentage score was 95%. The review results by learning media experts obtained an excellent category and the percentage score was 91.6%. Besides, the results of individual testing obtained an excellent category and the percentage score was 98.4%. The results of the small-group testing obtained an excellent category and the percentage score was 97.5%. Therefore, this study revealed that learning videos based on micro-learning principles sat in the excellent qualifications and were suitable to be implemented as supporting learning activities to establish more interesting and enjoyable activities.